STUDI KUALITATIF TENTANG MANFAAT DAN KERUGIAN DALAM PENYUSUNAN LAPORAN KEUANGAN PADA UD MITRA PELITA - Mandey, Maurenthia J.; Saerang, David P. E.; Pusung, Rudy J. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
The financial statements are fundamental for every company, both large companies and small companies. In Indonesia, according to the Ministry of Cooperatives and Micro Small and Medium Enterprises, up to 2013 the total number of business units is 57,900,787, SME’s with the largest business units as much as 57,895,721 (99.99%) and large enterprises as much as 5.066 (0.01%). The development of SME’s is only seen in the number, while in the financial aspect, SME’s still lags behind. This condition is also experienced by UD Mitra Pelita who have not prepared financial statements. The purpose of this study is to know how the financial management of UD Mitra Pelita and their views on the benefits and losses in the preparation of financial statements as well as the factors that the reason the owner of the company has not compiled or not prepare financial statements. The method of analysis used in this research is descriptive method with case study design. The results showed that the financial management of UD Mitra Pelita the same as SME’s in general that is not yet prepared financial report. This raises many problems in their business activities. The factors that cause UD Mitra Pelita has not compiled financial statements are not much different from SME’s in general. However, these factors are not a barrier for UD Mitra Pelita to implement financial reports that have many benefits for their business activities. Keywords:Financial Reports, Benefits, Losses, Factors.